Dual-functionalization based on combination of quercetin compound and rare earth nanoparticle - 王坤杰 吴龚平 李红霞 李明亮 张德懿 冯辉霞 范海燕 (Journal of rare earths, 2013)
While the nanoparticles like La2O3 and other rare earth oxides were believed to be able to provide effective scavenging hydroxyl radical. Quercetin, a hydrophobic agent, showed some potential antibacterial activity. The present work successfully performed the surface modification of rare earth nanoparticle using facile and general strategy. In specific, the hydrophobic quercetin was grafted on the rare earth nanoparticle through the coupling with silane. The surface modified nanoparticle was characterized by Fourier-transform infrared （FTIR）, thermogravimetric analysis （TGA）, and scanning electron microscopy （SEM）. The surface modification helped to retain both the scavenging hydroxyl radical property of rare earth nanoparticle and the antibacterial activity of quercetin. This dual-function properties showed potential for application in the development of biomedicine such as antioxidant, anti-inflammatory, antibacterial and anticancer.